Overview of Fungi in the Sputum of Pneumonia Patients at Bendan Regional General Hospital, Pekalongan City - Dwi Melinda, Vadia; Riyanto, Agus (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Pneumonia remains one of the leading causes of morbidity and mortality, particularly among vulnerable groups such as children, the elderly, and immunosuppressed patients. In addition to being caused by bacteria and viruses, fungal infections can also exacerbate a patient's condition, but they are often overlooked because they are not always the primary focus of laboratory testing. This study aims to describe the morphology of fungi in the sputum of pneumonia patients at Bendan General Hospital in Pekalongan City as initial data that can be used to support earlier diagnosis of fungal infections. Method: This study is descriptive in nature, using direct microscopic examination with three methods: Gram staining, Lactophenol Cotton Blue (LPCB), and 10% Potassium Hydroxide (KOH). Sputum samples were collected purposively from pneumonia patients and examined at the AAK Pekalongan Microbiology Laboratory. Result: Out of 26 samples, 17 were positive for fungi (65.4%) using the Gram and LPCB methods. The KOH method showed 5 positive samples (19.2%). The fungal morphology observed included yeast cells (blastospores) and branched hyphae, consistent with the characteristics of fungi from the genus Candida spp. Conclusion: Microscopic examination using Gram and LPCB methods provided a more easily observable descriptive morphology of fungi, such as yeast cells and branched hyphae. Meanwhile, the KOH method yielded lower results (19.2%), possibly due to limitations in preparation techniques or the nature of the reagents, which did not clearly display fungal structures as effectively as other methods using additional stains. These findings emphasize the importance of direct microscopic examination as an initial step that can help identify the presence of opportunistic fungi in pneumonia patients and support clinical diagnosis considerations in the laboratory.